Ethical coaching and athlete transitions – A Foucauldian perspective on high-performance sports - Gerdin, Göran; Pringle, Richard (Frontiers in Sports and Active Living, 2025)
High-performance sport is often celebrated for cultivating discipline, resilience and excellence. Yet, the same structures that produce elite performance frequently rely on disciplinary practices that can compromise athlete autonomy, well-being and identity development. This article interrogates the ethical dimensions of coaching in high-performance sport through a Foucauldian lens, drawing on concepts such as disciplinary power, technologies of the self and the aesthetics of existence. Building on the work of Jim Denison and colleagues, as well as our own previous work, we examine how coaching practices shape athlete subjectivities both during and after elite sporting careers. The paper presents a framework that coheres a number of key concepts from existing coaching research and enriches them through a Foucauldian ethical perspective, offering a unified way of understanding the ethical dimensions of coaching. We argue that coaching must be reimagined as an ethical, relational and reflexive practice that goes beyond harm reduction to actively support athlete well-being and meaningful, sustainable transitions beyond sport. We explore how ethical self-creation can enable coaches to resist dominant norms and develop care-based coaching approaches that challenge the performance-at-all-costs ethos. We also consider how these insights align and contrast with existing youth sport philosophies and conclude by proposing a set of guiding principles for fostering ethical and sustainable coaching environments. In doing so, the paper offers a contribution to sport coaching research and practice by illuminating how coaches can engage in ethical self-work and systemic transformation, positioning athletes not only as performers but as whole persons capable of living meaningful lives in and beyond sport.